solutions_test3_section001_spring08

# solutions_test3_section001_spring08 - ECE 220 Test 3...

This preview shows pages 1–4. Sign up to view the full content.

ECE 220 Test 3 Solutions 14 April 2008 Problem 1. (20 points) A system is described by the diﬀerential equation given below: dv ( t ) dt + 4 v ( t ) = v s ( t ) (1) where v s ( t ) is the input. Let v s ( t ) = 10cos(5 t ) and v (0) = 0. Determine the solution in the Laplace domain; in other words, ﬁnd V ( s ). Solution Take Laplace Transforms (LT) of both sides of Equation 1. We have L " dv ( t ) dt + 4 v ( t ) # = L [ v s ( t )] sV ( s ) - v (0) + 4 V ( s ) = 10 s s 2 + 5 2 (2) sV ( s ) - 0 + 4 V ( s ) = 10 s s 2 + 5 2 V ( s ) = 10 s ( s 2 + 5 2 )( s + 4) In deriving Equation 2 we used the following facts: 1. The linearity property of the LT 2. The diﬀerentiation property of the LT: L " dv ( t ) dt # = sV ( s ) - v (0) 3. The LT of the cos function is L [cos(5 t )] = s s 2 + 5 2 So, ﬁnally, V ( s ) = 10 s ( s 2 +5 2 )( s +4) 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Problem 2. (20 points) The solution (in the Laplace domain) is given by: V ( s ) = 1 ( s + 4)( s 2 + 4) (3) Determine the solution in the time domain, i.e., ﬁnd v ( t ). Express v ( t ) as a real-valued signal. Solution The roots of ( s 2 + 4) are ± 2 j . Use Partial Fraction Expansion to rewrite Equation 3 as V ( s ) = K 1 s + 4 + K 2 s - 2 j + K * 2 s + 2 j (4) In Equation 4 we used the fact that the coeﬃcients K 2 and K * 2 are complex conjugates of each other. Now K 1 = ( s + 4) V ( s ) | s = - 4 = ( s + 4) 1 ( s + 4)( s 2 + 4) | s = - 4 = 1 ( s 2 + 4) | s = - 4 = 1 (16 + 4) = 1 20 (5) K 2 = ( s - 2 j ) V ( s ) | s =2 j = ( s - 2 j ) 1 ( s + 4)( s 2 + 4) | s =2 j = 1 ( s + 4)( s + 2 j ) | s =2 j = 1 (2 j + 4)(2 j + 2 j ) = 1 4 j (4 + 2 j ) = 1 320 e (6) where θ = - tan - 1 ± 16 - 8 (7) Substitute Equations 5, 6 and 7 into Equation 4. We have V ( s ) = 1 20 1 s + 4 + 1 320 e 1 s - 2 j + 1 320 e - 1 s + 2 j and, in the time domain: v ( t ) = 1 20 e - 4 t u ( t ) + 1 320 e e 2 jt u ( t ) + 1 320 e - e - 2 jt u ( t ) 2
= 1 20 e - 4 t u ( t ) + 1 320 [ e 2

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 03/30/2009 for the course ECE 220 taught by Professor Nilson during the Spring '08 term at N.C. State.

### Page1 / 10

solutions_test3_section001_spring08 - ECE 220 Test 3...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online